2013
DOI: 10.1099/jmm.0.050617-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and follow-up of Bartonella henselae infection in the spleen of an immunocompetent patient by real-time quantitative PCR

Abstract: Systemic Bartonella henselae infections are unusual in immunocompetent adults. However, here we report one such case of bartonellosis in a 34-year-old patient, who presented with fever and multinodular splenomegaly. We also describe a novel method of identifying Bartonella henselae by real-time quantitative polymerase chain reaction and sequencing of amplified products. This could prevent splenic bartonellosis being mistaken for lymphoma and thereby avert unnecessary splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…31 , 34 Herein, we describe 3 new cases of HS-CSD and review 33 previously reported cases with a focus on clinical descriptions, diagnosis, and therapeutic approaches. 4 , 6 , 9 , 10 , 18 , 23 , 24 , 26 , 27 , 29 , 30 , 33 , 35 , 36 , 38 42 , 44 , 45 …”
Section: Introductionmentioning
confidence: 99%
“…31 , 34 Herein, we describe 3 new cases of HS-CSD and review 33 previously reported cases with a focus on clinical descriptions, diagnosis, and therapeutic approaches. 4 , 6 , 9 , 10 , 18 , 23 , 24 , 26 , 27 , 29 , 30 , 33 , 35 , 36 , 38 42 , 44 , 45 …”
Section: Introductionmentioning
confidence: 99%
“…PCR ND. Serology positive ND 2 weeks/NA Ciprofloxacine 2 week, CT-guided drainage, splenectomy Case 11 , 2013 [ 11 ] 34 F Abdominal pain, fever Multiple spleen abscess, skin lesion, lymphade NO WBC normal, CRP, and liver enzymes NA Abdomen MRI PCR and serology positive. Culture ND ND NA/2.5 months AZT+DOX 5 d, CLR+RIF 5 weeks Case 12 [ 12 ], 2012 36 F Abdominal pain, fever 5 cm right hepatic lobe mass NO WBC normal, CRP NA, liver enzymes elevated Abdomen CT Culture positive.…”
Section: Methodsmentioning
confidence: 99%
“…A homemade real-time PCR with SYBR Green 1 dye was performed as previously described [ 3 , 4 ]. Briefly, DNA extraction from whole blood was carried out using the QIAamp DNA Blood Mini Kit (QIAGEN ® Group) according to the manufacturer’s instruction.…”
Section: Methodsmentioning
confidence: 99%